Comprehensive Program for the Induction of Artificial Intelligence Knowledge in Secondary Education: Case of Neural Networks, Fuzzy Logic and Image Processing - Chacón-Castro, Marcos (2024)
The education demand in the Artificial intelligence (AI) area does not have solutions in the traditional teaching methods. It is important to implement new educative strategies which are able to cover these new demands. Moreover, the industry, the company, health, transport and culture, boost by the new tech- nologies which use AI, constantly change. This happens mainly in the field of neuronal networks, Fuzzy logic, digital image processes, but this process does not happen in the education in the technological scenario. The researcher witnesses the gap between the fast growth of the digital technologies and the growth of theories, strategies, teaching methods in these aspects in the middle education. The purpose of this paper is to propose an induction and reinforcement program of basic knowledge about AI in middle education in the neuronal network, fuzzy logic, digital image processes field. We plan the following phases: 1. Describe the relevant information. 2. Select teaching strategies to allow to stimulate and rein- force knowledge about artificial intelligence in middle education. 3. Design the practical AI teaching scenarios in middle education. 4. Make a proposal about an integral program as induction of knowledge about artificial intelligence in middle education in the case of neuronal networks, fuzzy logic and digital image pro- cesses. We take data from perception evaluations and specialized literature. This work intends to reduce the gap between the appearance of new technologies and the AI teaching in middle school.